The panorama of the circular economy in Brazil: a bibliometric study (Research, Society and Development, 2022)
The circular economy is a new area of knowledge and has been gaining interest from researchers, government and industries due to the impact generated by the current consumption model that has been degrading the ecosystem in the face of the challenge generated by climate change. In this research, a bibliometric analysis was carried out in order to evaluate the trends and characteristics of scientific publications on the subject. Bibliometric data were obtained by consulting the scientific databases Scopus and Web of Science, which in turn were analyzed by the authors, and only articles that were related to the main research topic were considered. The results were compiled, analyzed and presented in the form of figures, graphs and tables – generated by using Microsoft Excel and VOSviewer software for the construction of some illustrations. Finally, the study allowed us to conclude that research on circular economy is incipient, in terms of scientific research, particularly in the Brazilian context, despite a slight growth in the number of publications related to the topic in recent years. Another aspect that can be seen was that the largest number of publications focuses on issues related to the technical cycle, with room for advances in biological cycle themes, especially in the Brazilian case, due to its biological biodiversity.